Galaxy Zoo: Building the low-mass end of the red sequence with local post-starburst galaxies - Wong, O; Schawinski, K; Kaviraj, S; Masters, K; Nichol, R; Lintott, C; Keel, W; Darg, D; Bamford, S; Andreescu, D; Murray, P; Raddick, M; et al. (2012)
We present a study of local post-starburst galaxies (PSGs) using the photometric and spectroscopic observations from the Sloan Digital Sky Survey and the results from the Galaxy Zoo project. We find that the majority of our local PSG population have neither early- nor late-type morphologies but occupy a well-defined space within the colour-stellar mass diagram, most notably, the low-mass end of the 'green valley' below the transition mass thought to be the mass division between low-mass star-forming galaxies and high-mass passively evolving bulge-dominated galaxies. Our analysis suggests that it is likely that local PSGs will quickly transform into 'red', low-mass early-type galaxies as the stellar morphologies of the 'green' PSGs largely resemble that of the early-type galaxies within the same mass range. We propose that the current population of PSGs represents a population of galaxies which is rapidly transitioning between the star-forming and the passively evolving phases. Subsequently, these PSGs will contribute towards the build-up of the low-mass end of the 'red sequence' once the current population of young stars fade and stars are no longer being formed. These results are consistent with the idea of 'downsizing' where the build-up of smaller galaxies occurs at later epochs. © 2012 CSIRO Monthly Notices of the Royal Astronomical Society © 2012 RAS.